Toxic epidermal necrolysis induced by radiotherapy - Owczarczyk-Saczonek, Agnieszka B.; Placek, Waldemar J.; Rybak-d'Obyrn, Joanna; Wygonowska, Ewa (Dermatology Review/Przegląd Dermatologiczny, 2013)
Introduction . Toxic epidermal necrolysis (TEN) or Lyell syndrome is a life-threatening adverse drug reaction, characterized by widespread erythema, necrosis, and bullous detachment of the epidermis and mucous membranes. The estimated mortality associated with this illness varies widely in different reports, from 30–40%. In 90% of cases is associated with the exposure to the drug. Radiotherapy rarely triggers the illness. Objective . Presentation of the TEN provoked by radiotherapy. Case report. We present a case of 82-year-old patient with TEN provoked by radiotherapy which was used to treat a cancer of bladder. On admission the lesions covered about 60% of the total body surface area, involving oral mucosa and conjunctiva. Fever and oliguria were observed. Diagnostic investigation revealed leukocytosis, increased level of creatinine, glycosuria and proteinuria. After treatment with cyclosporine, 4 mg/kg, and metylprednisolon 48 mg, the skin, oral mucosa and conjunctiva lesions were cured within 3 weeks and there was the normalization of laboratory abnormalities. Conclusions. In some cases reported in literature, patients with primary and metastatic brain tumors develop TEN after treatment with phenytoin and its derivatives combined with radiation therapy. Such a reaction is called EMPACT (erythema multiforme associated with phenytoin and cranial radiation therapy). The development of TEN after radiation therapy is seldom reported.